DIVERSIFIKASI SAMBAL IKAN TANDIPANG ASAP DALAM JAR - Adi Suseno; Dyah Ayu Rakhmayeni; Meilya Suzan Triyastuti; Fernando Wowiling (Politeknik Kelautan dan Perikanan Bitung, 2021)
Tandipang fish sauce is one of the diversified products of tandipang fish. The choice of chili sauce as a diversified product is based on the reason that chili sauce is a popular product among the public and is quite in demand, especially the people of North Sulawesi. The purpose of this study was to make tandipang fish sauce products in jars and obtain the best quality and shelf life of tandipang fish sauces in jars. The benefits produced are as souvenirs of processed products typical of North Sulawesi. The method used is the experimental design used, namely the Factorial Completely Randomized Design (CRD) using ANOVA. Observation factors were storage time 0, 1, 2, and 3 weeks at a temperature of 28°C (room) and chili flavor variants (onion sauce, green chili sauce, and grilled rica). vary. Based on the results of the water content test, roasted rica is the best product. Because it has a low water content compared to chili and green chili sauce. Based on the results of organoleptic and microbiological tests, the tandipang fish sauce is suitable for consumption until the 3rd week. It can be concluded that the three variants of the tandipang fish sauce can be stored for 3 weeks at room temperature.Keywords : diversification, jar, sauce, shelf life , tandipang fish